A mini-max problem for self-adjoint Toeplitz matrices - Courtney, Dennis; Sarason, Donald (MATHEMATICA SCANDINAVICA, 2012)
We study a minimum problem and associated maximum problem for finite, complex, self-adjoint Toeplitz matrices. If A is such a matrix, of size (N+1)-by-(N+1), we identify A with the operator it represents on P_N, the space of complex polynomials of degrees at most N, with the usual Hilbert space structure it inherits as a subspace of L^2 of the unit circle. The operator A is the compression to P_N of the multiplication operator on L^2 induced by any function in L^∞ whose Fourier coefficients of indices between -N and N match the matrix entries of A. Our minimum problem is to minimize the L^∞ norm of such inducers. We show there is a unique one of minimum norm, and we describe it. The associated maximum problem asks for the maximum of the ratio of the preceding minimum to the operator norm. That problem remains largely open. We present some suggestive numerical evidence.